COVID-19 crisis and role of the Indian state. (4th October 2021) - Pathak, Abhijit; Chattopadhyay, Apurba Kumar
COVID-19 has affected the world with varied intensity and India is no exception. The lockdown measures implemented in India to combat COVID-19 rendered significant economic costs in terms of loss of employment, income, and output. In this paper, we find that the national lockdown measures adopted by the GOI have weakened the states financially, making them financially more dependent on the centre. This paper argues that the interests of domestic capitalists and international finance capital have restricted India from increasing its government expenditure and adopting economic policies for the best benefits of its citizens. Thus, financial weakness of the state governments has accentuated during the lockdown period and has tilted the balance further in favour of the centre. This is neither encouraging from the perspective of fiscal federalism in India nor for the delivery of welfare to its citizens. This may even delay the process of India's economic recovery.